Studi Numerik dan Eksperimen Aerodinamika Airfoil NACA 24112 - Perdana, Dhedhek Wahyu Aji; Effendy, Marwan (Creative Research in Engineering (CERIE), 2021)
This study aims to investigate experimentally and numerically the characteristics of the NACA 24112 airfoil. This study focuses on investigations of lift coefficient (CL), drag coefficient (CD), andÂ CLÂ /Â CDÂ ratio and pressure, including flow visualisation around the airfoil. The study was conducted at an angle of attack ranging to -15Â°-20Â° and various Mach number atÂ 0.0728 and 0.0809. The experimental test used a test specimen with a span dimension of 20 cm and a chord of 10 cm with an open wind tunnel. A total of 376,500 square elements with values âˆ†y + to 9.6 were successfully generated to achieve the accuracy of the simulation. The results showed that theÂ CLÂ andÂ CDÂ values obtained from the experimental and simulation results showed a similar trend. TheÂ CDÂ value of the experimental results is greater than the simulation results. TheÂ CLÂ andÂ CDÂ values will increase with increasing flow velocity and increasing the angle of attack. A stall occurs at an attack angle of 20Â°.